RESEARCH TRENDS ON THE DEVELOPMENT OG AUGMENTED REALITY (AR)-BASED INTERACTIVE LEARNING MATERIALS TO IMPROVE LEARNING OUTCOMES FOR ELEMENTARY SCHOOL: A BIBLIOMETRIK ANALYSIS (2022-2026) - Damayanti, Aulia; Nuni Widiarti; Bambang Subali; Ellianawati; Tri Joko Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has had an impact on the learning system in primary schools and increased pupils’ screen time. Currently, teachers in Indonesia still lack adequate digital competence, which is one of the factors affecting pupils’ learning outcomes. This study aims to analyse research trends regarding the development of Augmented Reality (AR)-based interactive learning media to improve the learning outcomes of primary school students using a bibliometric approach. Data were obtained from 37 documents indexed in the Scopus database from 2022-2026. Data analysis was conducted using the Scopus Analyze feature and VOSviewer software. The results indicate a significant increase in the number of publications, particularly between 2023 and 2025. Indonesia is the country contributing the most publications. Social Sciences is the dominant field of study. Keyword co-occurrence analysis identified three main clusters related to the implementation of AR in learning, the effectiveness of AR technology use, and the impact of AR on learning outcomes. Furthermore, overlay visualisations indicate a shift in research trends towards the use of technology in learning and the application of Augmented Reality in primary schools. Overall, these findings suggest that research on Augmented Reality in primary education continues to evolve and still offers ample opportunities for future studies within different educational contexts.